The bioequivalence of a single intravenous administration of the anesthetic alfaxalone in cyclodextrin versus alfaxalone in cyclodextrin plus preservatives in cats. Issue 3 (19th January 2018) - Pasloske, K.; Ranasinghe, M. G.; Sauer, S.; Hare, J.
Abstract : To demonstrate the bioequivalence of alfaxalone in cyclodextrin (Reference Product) to a formulation of alfaxalone in cyclodextrin also containing the preservatives ethanol, chlorocresol, and benzethonium chloride (Test Product) when administered for the purpose of inducing anesthesia in the cat. Blinded, single‐dose, randomized, two‐period, two‐sequence, cross‐over bioequivalence study with a 7‐day washout period between treatments. Twenty‐four (12 neutered males and 12 intact females), healthy, adult cats weighing 4.1±0.9 kg. Cats were administered 5 mg/kg IV of alfaxalone in the Reference or Test Product using a randomized cross‐over design. One‐milliliter venous blood samples were collected at predetermined time points to 12 hr after drug administration to determine alfaxalone plasma concentration over time. Alfaxalone concentrations were determined by a validated analytical testing method using HPLC‐MS/MS. Plasma profiles of alfaxalone concentration against time were analyzed by noncompartmental analysis. The pivotal variables for bioequivalence were AUClast and C max . Equivalence was achieved if the 90% confidence interval for AUClast and C max fell into the asymmetric ±20% interval (0.80–1.25). Physiological variables, quality of anesthesia visual analog scale (VAS) scoring and anesthetic event times were recorded. ANOVA or ANCOVA (single time point), RMANOVA or RMANCOVA (multiple time point) was used for normally distributed data. GLIMMIX was used for nonnormally distributed data. VAS scores were analyzed as for blood bioequivalence data. Variables were evaluated for safety and assessed at alpha = 0.10. C max and AUClast for Reference and Test Products were statistically bioequivalent. No physiological variables except for a drug by time interaction for respiratory rate differed between treatment groups, and this difference was not clinically relevant. No anesthetic event times or VAS scores for quality of anesthesia were different between treatment groups. Neither formulation caused pain upon injection. The Reference and Test Products are pharmaceutically bioequivalent formulations when administered as a single intravenous administration for the purpose of induction of anesthesia in cats.